2011
DOI: 10.1179/1743289810y.0000000025
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nanoclays on mechanical and barrier properties of hydrogenated acrylonitrile butadiene rubber nanocomposites

Abstract: In this research, two different methods have been investigated for optimising the preparation of hydrogenated acrylonitrile butadiene rubber/clay nanocomposites. Commercially available organoclay (Cloisite 20A) has been considered for the preparation of rubber nanocomposites. A detailed analysis has been made to investigate the morphological structure and mechanical behaviour at room temperature and at elevated temperature. Also the influence of organoclays on permeability has been studied. Structural analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
(36 reference statements)
0
17
0
Order By: Relevance
“…Various types of 2D particles have been incorporated into diverse elastomeric matrices to improve their barrier properties against gases and solvents. Natural or synthetic layered silicates, such as montmorillonite (MMT), rectorite clay (REC), cloisite and vermiculite clay, have also been extensively studied as nanofillers for elastomers to lower their permeabilities[279][280][281][282][283][284]. For example, the incorporation of 20-30…”
mentioning
confidence: 99%
“…Various types of 2D particles have been incorporated into diverse elastomeric matrices to improve their barrier properties against gases and solvents. Natural or synthetic layered silicates, such as montmorillonite (MMT), rectorite clay (REC), cloisite and vermiculite clay, have also been extensively studied as nanofillers for elastomers to lower their permeabilities[279][280][281][282][283][284]. For example, the incorporation of 20-30…”
mentioning
confidence: 99%
“…and . This variation is primarily due to the change in segmental mobility of the chains . However, compared to other elastomers, HNBR can still provide a fairly strong reinforcement at 150°C.…”
Section: Resultsmentioning
confidence: 99%
“…More details on the preparation methods can be found in our earlier publications. 15,16 To investigate the effects of silanes with nanoclays on the HNBR matrix, two different commercially available silanes, amino silane (AS) and sulfido silane (SS), were used. The masterbatch preparation followed has been the same as mentioned above.…”
Section: Preparation Of Hnbr/c15a Nanocompositesmentioning
confidence: 99%
“…Our focus of research work here is to develop a new novel O‐ring material for sealing applications that can withstand high temperature and pressure at different harsh conditions. In recent times, our research team has reported improvement in the properties after reinforcing various other elastomers with nanoclays, such as ethylene propylene diene monomer,14 NBR,14 and HNBR 15–19. Other than developing a novel rubber seal material, the main purpose of our past research was to develop a novel way of dispersing nanoclays into the rubber matrix that is more suitable for industrial production line and formulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation